2013
DOI: 10.1186/1477-7819-11-253
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal schwannoma: a case report

Abstract: Most tumorous lesions of the esophagus are esophageal cancers. Benign primary tumors of the esophagus are uncommon, and account for approximately 2% of all esophageal tumors. More than 80% of benign esophageal tumors are leiomyomas, with schwannomas being rare. A 55-year-old woman visited our internal medicine department with complaints of palpitations and discomfort during swallowing. A chest computed tomography scan showed a lobulated tumor (75 × 57 × 80 mm) in the upper to middle mediastinum, with homogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 10 publications
0
44
0
3
Order By: Relevance
“…A few cases of primary esophageal schwannomas have been reported [3, 4]. Gastrointestinal schwannomas account for 0.4 to 1.0 % of all submucosal tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…A few cases of primary esophageal schwannomas have been reported [3, 4]. Gastrointestinal schwannomas account for 0.4 to 1.0 % of all submucosal tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The final diagnosis of benign esophageal schwannoma is based on histopathology and Otherwise, there are two tumors in the first case and there were no related reports in the previous studies. Chemotherapy and radiation therapy are ineffective, and the most common treatment is enucleation by surgery or endoscopy (1,9). In the cases we report here, we enucleated the tumor under thoracoscopy in the first patient and through right thoracotomy in the other two patients.…”
Section: Discussionmentioning
confidence: 99%
“…Benign schwannoma of the esophagus is rare, with leiomyomas accounting for 80% of cases (1). There have been only 28 reported cases in China in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal schwannomas are exceedingly rare with only a handful of cases reported in the literature [3]. A literature review performed for the past decade, 2005 -2015, revealed a total of 21 cases of which two cases were of concurrent esophageal schwannomas [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The surgical approaches to these include four thoracoscopic, six thoracotomy, five cervical approaches, and five esophagectomies or partial esophagectomies.…”
Section: Discussionmentioning
confidence: 99%